Complicações microvasculares no diabetes tipo 1: uma análise comparativa entre pacientes tratados com transplante autólogo não mieloablativo de células-tronco hematopoiéticas versus pacientes tratados com insulinoterapia convencional em cenário de mundo real - Sabóia, Jaquellyne Gurgel Penaforte (2017)
Type 1 diabetes mellitus (T1DM) is a chronic disease in which the best-established treatment is to control the blood glucose by intensive insulin therapy. However, several studies have shown that, in clinical practice, only a minority of diabetic patients, irrespective of types of insulin or dosing schedules, can maintain HbA1c goal. This poor control is associated with the development of microvascular complications. Autologous Nonmyeloablative Hematopoietic Stem Cell Transplantation (AHSCT) has been proposed as a way to preserve B-cell function, improves metabolic control and, possible, reduces microvascular complications in T1DM patients. However, there is no available data compared AHST to conventional therapy. The aim of this study was to explore the impact on microvascular complications, long term preservation of residual B-cell function and glycemic control of patients with T1DM treated with Autologous Nonmyeloablative Hematopoietic Stem Cell Transplantation (AHSCT) compared to real world conventional therapy. Cross-sectional data of patients treated with AHSCT were compared with patients who received conventional therapy from the BrazDiab1, the largest multicenter observational study in type 1 diabetes mellitus in Brazil. Median duration of diabetes was approximately 8 years in both groups. The presence of microvascular complications, residual β-cell function, through insulin-dose adjusted HbA1c (IDAA1C), A1c and insulin dose of patients were compared. After approximately 8 years of diagnosis, AHSCT- treated patients (n=24) presented no cases of microvascular complications while 21.5% (31/144) had at least one (p<0.005) complications in the conventionally treated group (n=144). Further, no case of nephropathy was reported from thein the AHSCT group while 13.8% were detected in the conventional group of the control population treated with conventional therapy were registered for the condition during the same period (p<0.005). With regard of residual β-cell function, the percentage of individuals with predicted higher C-peptide levels (IDAA1C ≤ 9) was about ten times higher on in the AHSCT group compared with then conventional group (75% vs 7.58.3%) (p<0.001). Among AHSCT patients, 54.1% (13/24) had HbA1c<7.0 compared to 13.1% in the conventional group (p<0.001). Thus, after 8 years of follow-up, patients with newly-diagnosed type 1 diabetes treated with AHSCT presented lower prevalence of microvascular complications, higher residual B-cell function and better glycemic control compared to BrazDiab1 group treated with conventional therapy. These findings support AHSCT to have enhanced therapeutic outcomes for T1DM. Keywords: Diabetes Mellitus, Type 1. Transplantation. Insulin.